Attitudes towards Physics Subjects based on the Norms of Scientists, Attitudes towards Investigations in Physics and The Adoption of Scientific Attitudes from Students of SMA N 11 Jambi City - Astalini, Astalini; Kurniawan, Dwi Agus; Farida, Linda Z.N.; Hendri, Menza (Phenomenon : Jurnal Pendidikan MIPA, 2020)
The purpose of this study is to describe student attitudes toward physics based on the indicators of scientific normality, attitudes toward inquiry in physics and adoption of students' scientific attitudes. The type of research used is quantitative type with survey method. This research subject are 235 students from science major in Senior High School 11 Jambi city. The instruments in this research is a questioner by Darmawangsa (2018). The results show that attitudes of high school 11 students tend to be good with a scientific normality category of 47%, attitudes toward inquiry in physics by 53% and adoption of scientific attitudes by 63%